Aerobic biodegradation of p-nitrophenol in a nitrifying sludge bioreactor: System performance, sludge property and microbial community shift. (1st July 2020) - Li, Mingrun; Wei, Dong; Yan, Liangguo; Yang, Qingwei; Liu, Lulu; Xu, Weiying; Du, Bin; Wang, Qian; Hou, Hongxun
Abstract: The system performance, sludge property and microbial community shift were evaluated in a nitrifying sludge (NS) bioreactor for simultaneous treating p -Nitrophenol (PNP) and high ammonia wastewater. After long-term acclimation for 80 days, the removal efficiencies of PNP and NH4 + -N reached to 99.9% and 99.5%, respectively. Meanwhile, the effluent PNP gradually decreased from 7.9 to 0.1 mg/L by acclimation of sludge. The particle size of NS increased from 115.2 μm to 226.3 μm accompanied by the decreased zeta potential as a self-protection strategy. The presence of PNP exposure altered the effluent soluble microbial products (SMP) fluorescent components and molecular composition. The increase in the relative abundance of Thauera, Nitrospiraceae and Nitrosomonas indicated the nitrification and denitrification capacities of NS increased, which maybe the PNP cometabolic biodegradation effect. Moreover, Ignavibacteria and Aeromonas were responsible as the dominant bacteria for degrading PNP in the nitrifying system. Graphical abstract: Image 1 Highlights: PNP was cometabolic biodegraded in the nitrifying system. The particle size of NS increased accompanied by the decreased zeta potential. PNP exposure altered the effluent SMP molecular composition. Ignavibacteria and Aeromonas were responsible for PNP biodegradation.